Temporary employment contracts in academia: a real option view. Issue 2 (3rd April 2017) - Brady, Malcolm
Abstract : This paper examines the strategic use of temporary employment contracts in dealing with supply uncertainty in the form of employee ability that is slow to reveal itself, for example in academia where there exist significant time lags in demonstration of research ability. A temporary contract is modeled as a real option, specifically as a combination of put option and stock, known as a protective put. The option price is modeled as relief from project work, e.g. teaching, and the exercise price is modeled as a target value, e.g. requisite number of publications. The model provides an explanation for contrasting use of temporary contracts in research and in teaching intensive institutions, and for teaching only and research only staff. The model has relevance in other employment situations where there is a time-lag between recruitment and revelation of employee ability, for example in young professional, top executive and political positions.